Trend Research of Studies on In Vitro Fertilization from 2013-2023: A Bibliometric Analysis - Herniyatun; Asaduddin, Akmal Zaki; Suwaryo, Putra Agina Widyaswara (Buletin Ilmu Kebidanan dan Keperawatan, 2025)
Infertility affects approximately 17.5% of couples of reproductive age, making it a significant global health concern. In Vitro Fertilization (IVF) is a critical medical intervention that involves retrieving eggs from the prospective mother, fertilizing them with sperm in a laboratory, and transferring the resulting embryos into the uterus. A bibliometric analysis was conducted to explore research trends in IVF, utilizing SCOPUS data from 2013 to 2023. The analysis identified 7,015 documents, revealing fluctuating publication trends, with a steady increase from 2015 to 2022 followed by a decline in 2023. These findings underscore the value of bibliometric studies in understanding research patterns and recent advancements in IVF. Future research should aim to improve IVF success rates by focusing on innovative techniques and addressing challenges in the field.